Population-based Surveillance for Medically Attended Human Parainfluenza Viruses From the Influenza Incidence Surveillance Project, 2010–2014. Issue 7 (July 2016) - Steffens, Andrea; Finelli, Lyn; Whitaker, Brett; Fowlkes, Ashley
Abstract : Background: Parainfluenza viruses (PIV) have been shown to contribute substantially to pediatric hospitalizations in the United States. However, to date, there has been no systematic surveillance to estimate the burden among pediatric outpatients. Methods: From August 2010 through July 2014, outpatient health care providers with enumerated patient populations in 13 states and jurisdictions participating in the Influenza Incidence Surveillance Project conducted surveillance of patients with influenza-like illness (ILI). Respiratory specimens were collected from the first 10 ILI patients each week with demographic and clinical data. Specimens were tested for multiple respiratory viruses, including PIV1–4, using reverse transcriptase–polymerase chain reaction assays. Cumulative incidence was calculated using provider patient population size as the denominator. Results: PIVs 1–3 were detected in 8.0% of 7716 ILI-related outpatient specimens: 30% were PIV1, 26% PIV2 and 44% PIV3. PIV circulation varied noticeably by year and type, with PIV3 predominating in 2010–2011 (incidence 110 per 100, 000 children), PIV1 in 2011–2012 (89 per 100, 000), dual predominance of PIV2 and PIV3 (88 and 131 per 100, 000) in 2012–2013 and PIV3 (100 per 100, 000) in 2013–2014. The highest incidence of PIV detections was among patients aged <5 years (259–1307 per 100, 000). The median age at detection for PIV3 (3.4 years) was significantly lower than the median ages for PIV1 (4.5 years) and PIV2 (7.0 years; P < 0.05). Conclusions: PIVs 1–3 comprise a substantial amount of medically attended pediatric ILI, particularly among children aged <5 years. Distinct seasonal circulation patterns as well as significant differences in rates by age were observed between PIV types. Abstract : Supplemental Digital Content is available in the text.